Effect of oxalic acid and salicylic acid treatments on the post-harvest life of temperate grown apricot varieties (Prunus armeniaca) during controlled atmosphere storage. (October 2022) - Batool, Mariya; Bashir, Omar; Amin, Tawheed; Wani, Sajad Mohd; Masoodi, FA; Jan, Nusrat; Bhat, Shakeel Ahmad; Gul, Amir
This study aimed at investigating the influence of different postharvest treatments with oxalic acid (OA) and salicylic acid (SA) on quality attributes and postharvest shelf life of temperate grown apricot varieties stored under controlled atmosphere (CA) storage conditions. After each treatment was given, the samples were stored in CA store maintained at a temperature of 0 °C, 90 ± 5% relative humidity, 5% oxygen and 15% carbon dioxide for 30 days. Results indicated that both OA and SA treatments significantly (p ≤ 0.05) retained total soluble solids, titratable acidity, color profile, ascorbic acid content and total phenolic content of apricot varieties and had a positive effect on antioxidant activity and texture of samples compared to control. However, carotenoid content was found to be higher in control. Both the treatments reduced chilling injury index, weight loss and decay percentage of samples. Moreover, it was found that SA treatment was the most effective treatment in maintaining visual color of apricots while OA maintained fruit firmness and effectively decreased the decay percentage and chilling injury index of apricot varieties. In conclusion, it was found that both OA and SA have the potential to extend storage life of apricots and maintain quality attributes of the crop during CA storage.